Imaging for biopsies - AlBalood, Musaad; Almeshal, Mohammed (International Journal Of Community Medicine And Public Health, 2018)
Positron emission tomography/computed tomography (PET/CT) imaging technique is considered to be an advanced technique that emerged recently and has been successfully used to guide several procedures like obtaining biopsies and ablating tumors. In this review, we will thoroughly discuss the indications, uses, and advantages of guiding biopsies with PET/CT techniques, with main focus on the field of oncology. PET/CT techniques are considered to be emerging imaging modalities that have significantly improved diagnostic accuracy of biopsies. The most important advantage of using PET/CT imaging to guide biopsies is its ability to provide accurate visualization of the lesion, with immediate assessment of the procedure following its end. On the other hand, this technique still has some limitations. Most importantly, the significant exposure to radiation to both the patient and the physician.